Playing Games to Earn Money: The Conceptual Framework of Interaction between Gender, Learning Styles, Problematic Gaming Behavior and Success-Economic Gain Motivation of Playing Games - Torralba, Edwin M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study identified the constructs of problematic gaming behavior that significantly impact the success-economic gain motivation of gamers. Furthermore, this study explored the role of gender, number of games played, and learning styles in problematic gaming behavior and the success-economic gain motivation of gamers using an online survey (N = 136). This study identified escape from adverse moods and preoccupation as the significant determinants of success-economic gain motivation of gamers. Escape from bad moods and preoccupation mediates the relationship between gamers' gender, number of games played, and success-economic gain motivation. Regression analysis reveals that active-reflective and sequential-global learning styles moderate the relationship between escapism, preoccupation, and success-economic gain motivation of gamers. The results suggest that the combination of active-global learning style and reflective-sequential learning style has the highest impact on the success-economic gain motivation of gamers. The results led to two conceptual frameworks that show how gender, learning styles, problematic gaming behavior, and success-economic gain motivation all play a role in game play.